Sifat Fisik Daging Domba Garut Jantan dengan Waktu Pemberian Pakan yang Berbeda - Rahayu, S.; Aditya, E. L.; Jamil, S. (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2015)
High ambient temperature in tropical, especially during the daytime of Garut lamb cause highlevel of stress and low productivity. To overcome it can be improved the management. If the feed is givenin the evening, its metabolism process will take place throughout the night with the lower temperature.This method is expected result the higher productivity include the meat quality. So the aim of thisstudy was to evaluate the influence of feeding time (morning and evening) toward the physical meatcharacteristics of Garut lamb. 12 Garut lamb were used. They were placed in 12 individual cages. Thisstudy used block randomized design. As treatment was feeding time. As feed was a mix of field grass andconcentrates (40:60). Data of physical meat characteristics were analyzed by t-test. The physical meatcharacteristics include value of pH, the ability to water bind, cooking loss, and score of meat colour werenot significant. Garut lamb that was given feed at morning time, significant resulted the meat with moretender (1.04 kg/cm2) than the feeding time at evening (1.59 kg/cm2) (P<0.05). It can be concluded thatthe physical meat characteristics (except meat tenderness) of Garut lamb were similar in both differentfeeding time. The treatment of different feeding time can be change the behaviour of Garut lamb.